2021
DOI: 10.1021/acs.cgd.1c00957
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Temperature-Dependent Mechanical and Thermal Properties of One-Dimensional Chain Structure Hg2Br2 Crystals for Infrared Acousto-Optic Device Application

Abstract: The long-wave infrared acousto-optic tunable filters (AOTFs) based on Hg2Br2 crystals have attracted much interest in space exploration and harmful chemical agent detection. However, the growth of large Hg2Br2 single crystals with high quality and optical homogeneity still remains a challenge, and the lack of temperature-dependent mechanical and thermal properties of this crystal hinders the further enhancement of acousto-optic performance in practical applications. In this context, Hg2Br2 crystals (Φ 35 × 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Though the Hg 2 I 2 crystals have a large acousto-optic figure of merit (3200 × 1.5 × 10 −18 s 3 g −1 ) and a wide spectral transmission range (0.5-40 μm), large-size Hg 2 I 2 crystals with high-quality are extremely difficult to obtain, and these crystals are prone to cleave because of their severe layered characteristics. 4 Therefore, Hg 2 Cl 2 and Hg 2 Br 2 crystals were chosen as the research objects in this work.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Though the Hg 2 I 2 crystals have a large acousto-optic figure of merit (3200 × 1.5 × 10 −18 s 3 g −1 ) and a wide spectral transmission range (0.5-40 μm), large-size Hg 2 I 2 crystals with high-quality are extremely difficult to obtain, and these crystals are prone to cleave because of their severe layered characteristics. 4 Therefore, Hg 2 Cl 2 and Hg 2 Br 2 crystals were chosen as the research objects in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the polarizing and acousto-optic materials above, one dimensional chain-like Hg 2 X 2 (X = Cl, Br, and I) crystals are a class of potential polarizing and acousto-optic materials with excellent performance in the long-wave infrared range, for their ultra-large birefringence (0.547@10.6 μm for Hg 2 Cl 2 crystals and 0.667@10.6 μm for Hg 2 Br 2 crystals) and wide transparent ranges (0.38-20 μm for Hg 2 Cl 2 and 0.42-30 μm for Hg 2 Br 2 ). 4 Some studies on crystal growth, property characterization and device fabrication of Hg 2 X 2 crystals have been reported. [5][6][7][8][9][10][11] In the early 1970s, Barta et al reported the growth, the polarizing prism design, the refractive index and the velocity of Hg 2 Cl 2 and Hg 2 Br 2 crystals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations